Study On The Suitability Of Industrial Estates In The Northern Region Of Medan City To The Carrying Capacity Of The Environment - Arini Chairunnisa; Ihsan Azhari; Abdi Sugiarto; Abdiyanto (International Journal of Society and Law, 2024)
Industrial estates in the northern region of Medan City are currently developing close to community settlements, which have the potential to have a negative impact on the environment and public health. These impacts include air and noise pollution, water and soil pollution, declining property values, increased crime problems, and environmental damage. Therefore, it is necessary to conduct a study on the suitability of industrial estates to the carrying capacity of the environment. This study aims to assess the suitability of industrial estates with the Carrying Capacity and Carrying Capacity of Ecosystem Services-Based Environment. The method used in this study is quantitative descriptive, which describes environmental characteristics and the phenomenon of industrial estate development. The results of the study show variations in land suitability in the northern region of Medan City. In Medan Belawan District, most of the land (1,566.22 hectares) is not suitable for industrial estates, while in Medan Deli, most of the land (1,358.26 hectares) is very suitable. Medan Labuhan District is dominated by suitable land (2,157.42 hectares), while Medan Marelan has an even distribution between very suitable and suitable land. In coastal reclamation areas, most of the land (262.46 hectares) is not suitable.